An integrated numerical model for investigating guided waves in impact-damaged composite laminates. (15th September 2017) - Zhang, B.; Sun, X.C.; Eaton, M.J.; Marks, R.; Clarke, A.; Featherston, C.A.; Kawashita, L.F.; Hallett, S.R.
Abstract: This paper presents a novel numerical technique that combines predictions of impact-induced damage and subsequent ultrasonic guided-wave propagation in composite laminates, with emphasis on the development and verification of the modelling framework. Delamination and matrix cracking are considered in the modelling technique, which is validated by experimental measurements on a carbon-fibre/epoxy plate using a drop-weight impact tower and a scanning laser vibrometer. Good agreement has been found between simulations and experiments regarding the impact response and global-local wavefields. Effects of these two damage modes, damage extent and multiple impacts on guided waves are studied using the modelling tool. Matrix cracking leads to lower wavefield scattering compared with delamination, particularly in un-damaged regions. The modelling strategy can provide valuable guidelines for optimising health-monitoring arrangements on composite structures that are susceptible to impacts, and the guided-wave model can also be integrated with other numerical models for predicting internal flaws in composite laminates.